2003
DOI: 10.1007/s00106-002-0712-y
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of obstructive sleep apnea syndrome (OSA) in patients with sudden hearing loss

Abstract: Patients who develop sudden hearing loss tend to have OSA more frequently than those in the control group owing to the similar risk factors for cerebral infarction and sudden hearing loss.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 17 publications
0
8
0
1
Order By: Relevance
“…We postulate that treating SDB might reverse hearing deficit on the apex and middle turns of the cochlea, rather than the basal turn, which is mainly worsened by the aging process [40]. Indeed, SDB had been reported associated with hearing problems and possibly sudden deafness [41]. Although the lowest oxyhemoglobin saturation at night sleep possibly the factor is affecting hearing impairment [16], AHI exhibited dose-responsively associated with hearing impairment at various frequencies in a previous huge study (~14,000 participants) [17].…”
Section: Discussionmentioning
confidence: 90%
“…We postulate that treating SDB might reverse hearing deficit on the apex and middle turns of the cochlea, rather than the basal turn, which is mainly worsened by the aging process [40]. Indeed, SDB had been reported associated with hearing problems and possibly sudden deafness [41]. Although the lowest oxyhemoglobin saturation at night sleep possibly the factor is affecting hearing impairment [16], AHI exhibited dose-responsively associated with hearing impairment at various frequencies in a previous huge study (~14,000 participants) [17].…”
Section: Discussionmentioning
confidence: 90%
“…In contrast, other studies find insomnia-related problems in older tinnitus patients in over 50% of cases (Lasisi and Gureje, 2011). Likewise, there seems to be an increased prevalence of sleep-related respiratory disorders in tinnitus collectives (Fischer et al, 2003; Herold et al, 2010). …”
Section: Resultsmentioning
confidence: 99%
“…More recently, Foster and Machala reported that some OSA patients exhibited brief spells of nonpositional vertigo recurring throughout the day which responded to CPAP treatment [10]. OSAS has also been linked to sudden sensorineural hearing loss [29,30]. However, in a large Korean study over 9 years, an association between OSAS and sudden sensorineural hearing loss could not be demonstrated [9].…”
Section: Discussionmentioning
confidence: 99%